GENDER DIVERSITY & DIVIDEND POLICY IN INDONESIA - Nabilah Asmaa, Mariyah (2024)
This research aims to empirically test the influence of gender diversity on the dividend policy in Indonesia. The data from all non-financial companies with 210 firm-year observations are used to see the relationship between gender diversity on the dividend policy. Using fixed effect model, the results show that gender diversity in board of directors does not have a significant effect on dividend policy while gender diversity in board of commissioners have negative and significant effect on dividend policy. This indicates that the female board of commissioners as the supervisory board focuses on using profits earned for company operations to increase company growth which will lead to a reduction in dividend payments.